Infrastructure Facilities in Tourism Village Management - Mega Putri Wulandari; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out about how the infrastructure in the management of the tourist village and the constraints in the infrastructure in the management of the tourist village. This research is a qualitative descriptive study with the technique of determining informants using purposive sampling. In this study, the informants were the village head of Besur, as the hortiary sector of Besur Agro Educational Tourism, as the secretary of Besur Agro Educational Tourism and also the farmer group community. The location of this research was carried out in Besur Village, Sekaran District, Lamongan Regency. Data collection techniques are interviews, observation, documentation and literature study. The data collection technique uses Miles and Huberman which consists of four components of analysis, namely, data collection, data reduction, data presentation, and drawing conclusions. the community in supporting the running of the Besur Agaro tourism village program, education is carried out for the development of tourist villages in the agricultural and plantation sectors by taking part in the management and development of agricultural cultivation land, in this case the active participation of the Besur Village community. Furthermore, community involvement in farmer group groups supports the community participation program. With the opening of stalls around the tourist attraction area to facilitate tourists in terms of eating and drinking. Constraints faced in community participation in the management of tourist villages in Besur Village, Sekaran District, Lamongan Regency, there are problems, namely in terms of facilities and infrastructure and in terms of funding the Besur agro-educational tourism object.